5-HMF induces anaphylactoid reactions in vivo and in vitro. (2020) - Li, Encan; Lin, Ni; Hao, Ruirui; Fan, Xiaoyu; Lin, Lin; Hu, Guang; Lin, Sheng; He, Jiuming; Zhu, Qingfen; Jin, Hongtao
Graphical abstract: Highlights: 5-Hydroxymethylfurfural induced anaphylactoid reactions on ICR mice and BN rats model. 5-Hydroxymethylfurfural induced degranulation of RBL-2H3 cells and P815 cells. 5-Hydroxymethylfurfural induces anaphylactoid reactions both in vivo and in vitro . 5-Hydroxymethylfurfural limits in related products should receive more regulatory attention. Abstract: Aim: Excessive exposure to 5-hydroxymethylfurfural (5-HMF), which is a common impurity in various sugar-containing products, induces serious side effects. Our previous study revealed that 5-HMF exerted immune sensitizing potential when injected into rodents. In this study, we explored 5-HMF mediated anaphylactoid reactions and its underlying molecular mechanisms. Methods: We investigated anaphylactoid reactions in Brown Norway (BN) rats and Institute of Cancer Research (ICR) mice to identify 5-HMF mediated in vivo anaphylactoid reactions. RBL-2H3 and P815 cell degranulation models were also established, and degranulation, enzyme-linked immunosorbent, filamentous actin (F-actin) microfilament staining, and western blot assays were performed in these cells. Results: We showed that 5-HMF induced anaphylactoid reactions by increasing blood vessel permeability in mice, and significantly elevating histamine (His) and glutathione peroxidase-1 (Gpx-1) levels in rat serum. Moreover, after incubation with 5-HMF, β-hexosaminidase (β-Hex), His, IL-4 and IL-6 levels were all significantly increased, thereby inducing cellular degranulation in RBL-2H3 and P815 cells. Finally, 5-HMF also upregulated Lyn, Syk, p38 and JNK protein phosphorylation levels. Conclusions: Our findings suggest that 5-HMF induces anaphylactoid reactions both i n vivo and in vitro, therefore 5-HMF limits in sugar-containing products should receive more regulatory attention.